-18k-6k=6+18k

Simple and best practice solution for -18k-6k=6+18k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18k-6k=6+18k equation:


Simplifying
-18k + -6k = 6 + 18k

Combine like terms: -18k + -6k = -24k
-24k = 6 + 18k

Solving
-24k = 6 + 18k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-18k' to each side of the equation.
-24k + -18k = 6 + 18k + -18k

Combine like terms: -24k + -18k = -42k
-42k = 6 + 18k + -18k

Combine like terms: 18k + -18k = 0
-42k = 6 + 0
-42k = 6

Divide each side by '-42'.
k = -0.1428571429

Simplifying
k = -0.1428571429

See similar equations:

| 1/4x+y=5 | | 61+x=36 | | 108=2x+20+2x | | x^3+6x^2-7x-42=0 | | X/4+8=-16 | | 61+x=25 | | -6t-8=16 | | 15x+5y=30 | | 3x+5+2=2x+27 | | X-14.29=25 | | 6-3b=18 | | 4k+3-2k=k+3 | | 4+x/3=-1 | | 3x/15=64/125 | | 5-10x+8x=15 | | -5d-4=2d+6 | | 1w+3w=48 | | 13x+18=5-7(1-x) | | 20*50-5*50+1= | | 3x+x+4=12 | | 2(4x+4)=72 | | 10x-4=2x+q | | 3-4X(5*6)=23-4 | | 5/3m=19/12 | | Pt+Prt=A | | 2/5x+1/6x=3/10x+1/3 | | 1/64x^12-4m^10 | | 12x+29=8x-7 | | -45x+21=36x+87 | | 4-3x+2=6 | | -7(n+3)-(1+8n)8= | | a+1/10=-1.5 |

Equations solver categories